2020
DOI: 10.1111/eva.13080
|View full text |Cite
|
Sign up to set email alerts
|

Rapid morphological change in multiple cichlid ecotypes following the damming of a major clearwater river in Brazil

Abstract: Anthropogenic alterations to an ecosystem can provide opportunities for studying how populations respond to rapid ecological change. Over the past 80 years, there has been mounting evidence that modifications to waterways can have immediate, and lasting, ecological consequences that may result in varying degrees of habitat destruction and fragmentation (Allan & Flecker, 1993;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 170 publications
(196 reference statements)
1
9
0
Order By: Relevance
“…Rawlings et al (2021) similarly reported patterns, with lake dwelling round gobies having deeper bodies; however, those authors found no differences in dorsal head shape when comparing individuals sampled among habitats. Morphological distinctions between lake a stream habitats have been similarly observed in other fish species, including the red shiner (Cyprinella lutrensis, Akin & Geheber, 2020;Franssen, 2011) and six cichlid species (Gilbert et al, 2020). The most common morphological change in those cases was a streamlining of body shape, as we observed with the reduction in body depth for CC round gobies; however, head shape from the dorsal perspective was not evaluated in any of the cited studies.…”
Section: Between-population Preservation Effectsmentioning
confidence: 59%
See 1 more Smart Citation
“…Rawlings et al (2021) similarly reported patterns, with lake dwelling round gobies having deeper bodies; however, those authors found no differences in dorsal head shape when comparing individuals sampled among habitats. Morphological distinctions between lake a stream habitats have been similarly observed in other fish species, including the red shiner (Cyprinella lutrensis, Akin & Geheber, 2020;Franssen, 2011) and six cichlid species (Gilbert et al, 2020). The most common morphological change in those cases was a streamlining of body shape, as we observed with the reduction in body depth for CC round gobies; however, head shape from the dorsal perspective was not evaluated in any of the cited studies.…”
Section: Between-population Preservation Effectsmentioning
confidence: 59%
“…For instance, a selective advantage for increased dispersal ability for colonizing species has led to rapid evolution in morphology, including for wing size in birds (Berthouly-Salazar et al, 2012), foot size in rodents (Forsman et al, 2011), and bone structure and size in cane toad (Hudson et al, 2016). For fish, body shape changes in response to environmental transitions between stream and lake habitats have been observed in several taxa, although the general patterns of those changes are not always consistent (Akin & Geheber, 2020;Franssen, 2011;Gilbert et al, 2020).…”
mentioning
confidence: 99%
“…Furthermore, the specimens analyzed come from dams on the principal course of the Grijalva River. Notably, there is evidence of environmental changes and reductions in gene flow being caused by dam construction, which may induce rapid morphological modifications in fish (Michel et al 2008;Franssen 2011;Perazzo et al 2019;Gilbert et al 2020). Additionally, while the Grijalva and Usumacinta basins share some biological and ecological characteristics, each basin has an independent biogeographical history (Elías et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Not all collections, for example, span a sufficient length of time to draw statistically robust comparisons between reference and altered states. The scarcity of reference collections has been a notable limitation of all before‐after studies so far undertaken on eco‐evolutionary responses of fish to impoundment (Cureton II & Broughton, 2014; Geladi et al., 2019; Gilbert et al., 2020). Notably, stronger inferences could have been drawn had pre‐ and post‐impoundment collections at the Claiborne site spanned similar lengths of time.…”
Section: Discussionmentioning
confidence: 99%
“…Gaining insight into the tempo of phenotypic change has proven to be more challenging in part because of the limited availability of historical collections that include decadal‐long time series of specimens obtained prior to and following dam construction. To our knowledge, only two studies (Geladi et al., 2019; Gilbert et al., 2020) have examined specimens collected before and after dam construction, but in both studies comparisons were limited to a single pair of time intervals (i.e. between a pre‐ and post‐impoundment collection), precluding the study of temporal characteristics of morphological change.…”
Section: Introductionmentioning
confidence: 99%